Taxes or subsidies to promote investment in green technologies for a supply chain considering consumer preferences for green products. (September 2022) - Yi, Yongxi; Wang, Yangyang; Fu, Chunyan; Li, Yuqiong
Highlights: Considering consumer preferences in comparison taxes and subsidies on green manufacturing. Demand is influenced by price, consumer preferences, and marketing efforts jointly. Subsidies promote green innovation better than taxes. Emissions tax may lead to increased profits for manufacturers and even the supply chain. Abstract: This paper investigates the impact of green subsidies and emissions taxes on the development of green technologies for a supply chain consisting of a manufacturer and a retailer. The manufacturer is responsible for green technologies investing, and the retailer is responsible for marketing and selling products to consumers with green preferences. The government is free to choose between emissions taxes or green subsidies to promote green technologies. The results show: (1) Subsidy policies provide a greater incentive for manufacturers to reduce pollution. (2) When the marginal cost of investment in green technology is low, or the marginal damage cost of pollution is high, green subsidies than emission taxes lead to higher profits for manufacturers. (3) Green subsidies lead to higher profits for retailers than emissions taxes when the marginal cost of investment in green technology is lower. (4) Manufacturers and even supply chains are more profitable with environmental regulations than without them. This finding verifies the existence of Porter's hypothesis. (5) If the marginal cost of green technology is low or the marginal damage cost of pollution is high, the government seeking to maximize social welfare should choose a green subsidy policy; otherwise, it should apply an emissions tax.